Meningkatkan Kemampuan Berbahasa pada Anak Usia 4-6 Tahun dalam Menghafal Rukun Iman Melalui Metode Pemberian Tugas (Resitasi) - Putri, Naufa Melati (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2022)
The background of this research is the lack of initial memorization skills in children at Nurul Huda Palaran Islamic Kindergarten. In this study the method of giving assignments (recitation). The purpose of this study was to find out how to improve language skills in memorizing the pillars of faith through the assignment method (recitation) in group B of Nurul Huda Palaran Islamic Kindergarten in the 2022-2023 academic year. This study uses the type of performance research. The number of children in group B of Nurul Huda Islamic Kindergarten in this study was 16 children. After carrying out the simulation of learning improvement in the first cycle and the second cycle, namely the success of using the assignment method (recitation) is to increase interest in learning, overall the teacher has carried out teaching and learning activities well in the process of improving learning, there is an increase in mastery of learning activities, and an increase in before holding learning improvement simulations. The results of this study indicate that the method of giving assignments (recitation) can improve memorization skills. This is indicated by the increased ability to memorize the Pillars of Faith in children.